The myth of native speakers and native speakerism in Costa Rica - Solís Sequeira, Stephanie (2021)
Speaking English has become the universal language which people use to communicate, nonetheless to what extent do second language learners should master English to the point of having “Native” like mastery. This essay inquires the problematic of native speakers and native speakerism and how it affects Second Language Learners (SLL) and Second Language Teachers (SLT). Also this essay describes some of the myths that exist behind the Native Speaker’s teaching methodology and sheds light on how these myths reproduce discrimination towards SLL/SLT.